2020
DOI: 10.1590/0366-69132020663802905
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured titanium dioxide for use in bone implants: a short review

Abstract: Titanium dioxide (TiO2) based nanostructured materials have shown great potential for use in implants thanks to their excellent physicochemical properties, such as high specific surface area, ability to elicit positive cell response, and stability in body fluids. However, there are few studies in the literature that focus on the use of nanostructured TiO2 to support cell growth and bone regeneration. The purpose of this survey is to review the state of the art of TiO2 for use in bone implants, as well as provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 187 publications
(282 reference statements)
0
2
0
Order By: Relevance
“…The result is consistent with previous studies, indicating that as the current density increases, it will dominate the formation process as well as the dissolution process of thinner nanotubular TiO 2 under the influence of F − ions [31][32][33]. Therefore, selecting the appropriate current density in the titanium dioxide anodization process is crucial.…”
Section: Surface Morphology Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…The result is consistent with previous studies, indicating that as the current density increases, it will dominate the formation process as well as the dissolution process of thinner nanotubular TiO 2 under the influence of F − ions [31][32][33]. Therefore, selecting the appropriate current density in the titanium dioxide anodization process is crucial.…”
Section: Surface Morphology Analysissupporting
confidence: 90%
“…Due to its low wettability, the natural titanium material has limited applications in the biomedical field [5]. Therefore, the previous researches have been focused on improving the corrosion resistance and the biocompatibility of titanium by coatings it's with relatively thick TiO 2 layers [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The anatase phase is more electroactive than the rutile phase, having greater genotoxicity and photocatalytic effects [60][61][62][63]. The TiO 2 NCs have shown great potential for use in implants due to their excellent physical, chemical, and biological properties, such as high specific surface area, ability to provoke positive cellular response and stability in body fluids, is suitable for the propagation, proliferation, and differentiation of osteoblast cells [56,64]. Thus, will show exciting results obtained by the group using TiO 2 nanocrystals as well as their luminescence bio-location.…”
Section: (A) Cdse/cds Msqds Immobilized On a Gold Electrode Modified ...mentioning
confidence: 99%
“…2 CURRENT CONCEPTS REVIEW SOUBORNÝ REFERÁT have shown great potential for their use in implants, mainly due to their excellent physicochemical properties (such as high specific surface area, ability to elicit a positive cellular response and stability in body fluids). Athin layer of such surface treatment could help reduce undesirable side effects of titanium/titanium alloys implants by preventing or reducing the release of any of the metals present in the implant into organism (21) The normal titanium serum level is 0.06 µg/L. Several studies reported elevated titanium levels in patients after hip replacement and many times increased levels in case of implant failure.…”
Section: Introductionmentioning
confidence: 99%